(untitled) (Research, Society and Development, 2021)
Meat is a very important food for the Brazilian population and its economic sector. The consumption of ground meat has increased dramatically three decades ago, both in developed and developing countries, given the fact that it is low cost, as well as a better and more convenient way to enjoy less noble meats. This research aimed to evaluate the hygienic-sanitary quality of ground meat sold in a city located in the interior of Paraíba. To this end, six samples of this type of meat were collected in different places, in addition to denoting points of sale with contamination. For physical-chemical analyzes, water activity, acidity, pH and humidity of the product were tested. For the microbiological analyzes, the parameters recommended by the current legislation were followed. Samples C, D, E and F confirmed their presence for Salmonella spp. For the coliform group, only samples C, E and F were at risk for their presence, while for Staplhylococcus aureus, all analyzes showed negativity. Regarding the physical-chemical characterization, the values ​​showed susceptibility of these meats to the proliferation of bacteria, since the humidity was shown to be high and the acidity content turned to neutral. This study shows the importance of an analysis of quality control and safety in consumption for these meats and invokes the need for recurrent work of good handling practices with traders in an attempt to minimize contamination.